Introduction of highly resistant bacteria into a hospital via patients repatriated or recently hospitalized in a foreign country. (21st March 2014) - Birgand, G.; Armand‐Lefevre, L.; Lepainteur, M.; Lolom, I.; Neulier, C.; Reibel, F.; Yazdanpanah, Y.; Andremont, A.; Lucet, J. C.; Cantón, R.
Abstract We describe the prevalence of carriage and variables associated with introduction of highly drug‐resistant microorganisms (HDRMO) into a French hospital via patients repatriated or recently hospitalized in a foreign country. The prevalence of HDRMO was 11% (15/132), with nine carbapenamase‐producing Enterobacteriaceae, nine carbapenem‐resistant Acinetobacter baumannii and six glycopeptide‐resistant enterococci. Half of the admitted patients (63/132, 48%) were colonized with extended spectrum beta‐lactamase‐producing Enterobacteriaceae (ESBLPE). Among the four episodes with secondary cases, three involved A. baumannii.